Petiolar anatomy in some Rhamnaceae - D.A. Patil2, S.B. Shisode1* and (Current Botany, 2011)
The present paper deals with the anatomy of 13 species belonging to seven genera of family Rhamnaceae. The anatomical characters of the petiole such as petiole outline, epidermal characteristics, number of layers of parenchyma cells in the cortex, pattern of vascular system, occurence of crystals, tannin, etc. provide data to distinguish the taxa investigated